Assessing the impacts of large‐scale offshore wind power in Southern China. Issue 1 (20th October 2020) - Lin, Chenyun; Song, Yi; Zhao, Junhua; Liang, Gaoqi; Qiu, Jing
Abstract: As an important renewable energy resource, wind power has been greatly developed in Southern China to meet the increasing demands. In the context of power industry deregulation and hence electricity market development, wind power introduces new uncertainties for market participants and affects the long‐term planning of the power system concerned. In this paper, we use a simplified Guangdong power system model to simulate the electricity market in Southern China from 2019 to 2028. To study the economic and reliability impacts of installing large‐scale offshore wind farms, case studies are conducted to simulate two targeted scenarios, that is, with and without offshore wind power penetration. Based on the presented model, the well‐established Monte Carol simulation method is applied to assess the reliability of the Guangdong power grid by calculating the expected unsupplied energy (EUE). The experimental results show that the integration of offshore wind power farms will reduce the locational marginal prices (LMPs) as well as the weighted average spot price. The power flow on transmission lines with nodes connected to offshore wind farms will increase and the increase rate is higher in cases with higher demand. In addition, the increased EUE indicates that the integration of large‐scale offshore wind power farms will impair the reliable operation of the power grid. The proposed system model delivers practical references to renewable energy evaluation and regional electricity market operations.